The Effect of Ladder Drill and Zig-Zag Run Exercises and Motivation on Crescent Kick Performance in Young Athletes: A Health and Fitness Perspective - Iqlal Kahfi; Aldo Naza Putra; Bafirman Bafirman; Ahmad Chaeroni (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
This study tackles the issue of enhancing athletic performance in Pencak Silat, particularly in the execution of the crescent kick, a technique that demands agility, strength, and coordination. It is known that physical conditioning and motivation can affect how well an athlete performs. Nevertheless, limited research investigates the impact of training methodologies and motivational levels on martial arts performance. To examine this, a quasi-experimental design was utilized, testing two physical training methods (Ladder Drill and Zig-Zag Run) and two motivation levels (high and low) on 40 athletes (20 male and 20 female) from the IKSPI Kera Sakti club. The study employed a 2x2 factorial design, utilizing crescent kick ability as the dependent variable and motivation as a moderating variable. The results showed that the main effects of training methods and motivation levels on crescent kick ability were not statistically significant (p >0.05). However, the overall model explained 92% of the variance in performance (Adjusted R? = 0.905), which shows that both physical training and motivation had a strong effect on performance. Tests for normality and homogeneity of variance showed that the assumptions for parametric analysis were met, which made sure that the results were reliable. This study emphasizes that the amalgamation of physical conditioning and psychological support not only improves athletic performance but also fosters the physical and mental well-being of adolescents, thereby advancing overarching objectives in health promotion. To get the best results in sports and long-term health, you need to look at all of these factors together. Subsequent research ought to incorporate larger sample sizes and longitudinal methodologies to investigate the enduring effects of such interventions on youth development?Keyword: Pencak Silat, Crescent Kick, Physical Conditioning, Motivation, Ladder Drill, Zig-Zag Run